Mechanical, morphological, thermal and the attenuation properties of heavy mortars doped with nanoparticles for gamma-ray shielding applications - Alresheedi, Mohammed Thamer; Elsafi, Mohamed; Aladadi, Yosef T.; Abas, Ahmad Fauzi; Ganam, Abdullrahman Bin; Sayyed, M. I.; Mahdi, Mohd Adzir (Multidisciplinary Digital Publishing Institute, 2023)
This study aimed to develop a mortar composite with improved gamma ray shielding properties using WO3 and Bi2O3 nanoparticles, as well as granite residue as a partial replacement of sand. The physical properties and effects of sand substitution and nanoparticle addition on the mortar composite were analyzed. TEM analysis confirmed the size of Bi2O3 and WO3 NPs to be 40 ± 5 nm and 35 ± 2 nm, respectively. SEM images showed that increasing the percentage of granite residues and nanoparticles improved the homogeneity of the mixture and decreased the percentage of voids. TGA analysis indicated that the thermal properties of the material improved with the increase in nanoparticles, without decreasing the material weight at higher temperatures. The linear attenuation coefficients were reported and we found that the LAC value at 0.06 MeV increases by a factor of 2.47 when adding Bi2O3, while it is enhanced by a factor of 1.12 at 0.662 MeV. From the LAC data, the incorporation of Bi2O3 nanoparticles can greatly affect the LAC at low energies, and still have a small but noticeable effect at higher energies. The addition of Bi2O3 nanoparticles into the mortars led to a decrease in the half value layer, resulting in excellent shielding properties against gamma rays. The mean free path of the mortars was found to increase with increasing photon energy, but the addition of Bi2O3 led to a decrease in MFP and better attenuation, making the CGN-20 mortar the most ideal in terms of shielding ability among the prepared mortars. Our findings on the improved gamma ray shielding properties of the developed mortar composite have promising implications for radiation shielding applications and granite waste recycling.